CYBER PEDAGOGY, EDUCATIONAL TRANSFORMATION IN THE DIGITAL ERA: SYSTEMATIC LITERATURE REVIEW: Cyber Pedagogy, Transformasi Pendidikan di Era Digital: Systematic Literature Review - I DEWA AYU EKA PURBA DHARMA TARI; Made Hery Santosa; I Gde Wawan Sudatha; I Kadek Suartama (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Digital transformation in education, particularly post-COVID-19, has accelerated a major shift towards online learning. While it offers flexibility, this transition has also had significant impacts on students' mental health, including stress, anxiety, and digital burnout due to intense virtual interactions. This study aims to examine the relationship between cyber pedagogy, digital burnout, and students' mental health in the context of online learning. Using a Systematic Literature Review (SLR) approach, this research collected and analyzed 11 articles published between 2015 and 2025 through the Scopus, Web of Science, and Google Scholar databases. The analysis process was conducted following the PRISMA guidelines, focusing on the relationship between cyber pedagogy and its impact on students' mental health. The results show that digital burnout and mental health disorders are significant challenges often overlooked in digital learning design. Cyber pedagogy, with proper management, can help reduce the psychological gap between students and the learning environment, while also improving students' well-being. This study emphasizes the importance of a more responsive and humanistic pedagogical approach in designing digital learning, which not only focuses on technical aspects but also supports students' mental health sustainably.